Antimicrobials and antimicrobial resistance - Laxton, Claire S. (2018)
In order to curb the concerning rise in antimicrobial resistance, novel antimicrobials, particularly against multi-drug resistant Gram-negative bacteria, must be developed. The Gram-negative outer membrane (OM) and its biosynthetic pathways presents a number of promising drug targets. The OM is complex and asymmetrical, with an outer leaflet packed lipopolysaccharide (LPS) which provides an impermeable barrier against various antimicrobials. Asymmetry is thought to be maintained by the Mla system, a multiprotein complex which removes outer-leaflet OM phospholipids, traffics and reinserts them into the inner membrane (IM). Firstly, this thesis examines the IM MlaFEDB complex, and periplasmic MlaC. Quartz crystal microbalance and thin layer chromatography were used to examine a MlaFEDB-tethered bilayer model, to determine the directionality of transfer of phospholipid at the IM. Strikingly, MlaC was shown to acquire, rather than deposit, phospholipid from MlaFEDB at the membrane, suggesting that the Mla system is involved in anterograde, rather than retrograde phospholipid transport. This may constitute a novel pathway in which phospholipids are trafficked to the OM, for which no mechanism is currently understood. Secondly, the development of an LPS-containing membrane model using the phospholipid 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), and its amenability for experiments using solid state magic angle spinning NMR, was explored. DMPC was found to be a potentially useful substitute for more fluid lipids in studying LPS structure and membrane dynamics. Moreover, this work reports the first successful 13C-labelling of smooth-type Escherichia coli LPS. These advances open avenues for developing a more biologically relevant, LPS-containing membrane model for studying the OM. This work could next be directly applied to replicating the MlaFEDB experiments on a model OM, with the OM component, MlaA, to better determine the directionality of phospholipid transport, and thus the overall biological function of the Mla system.